2012
DOI: 10.5402/2012/508649
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Full Blood Count Parameters Using Capillary and Venous Samples in Patients Presenting to the Emergency Department

Abstract: Full blood count (FBC) analysis is a common investigation done in the emergency department (ED). The aim of this study was to determine the accuracy of bedside FBC analysis using capillary blood samples from a finger stab at point of care (POC) compared to a conventional venous blood sample analysis. A total of 314 consecutive patients presenting to the ED were recruited. After consenting, a sample of the patient's venous (V) blood was obtained via venepuncture and sent to the haematology laboratory for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…White blood cells (WBC) and WBC content (neutrophils, eosinophils, basophils, lymphocytes and monocytes) were measured and corrected for change in plasma volume (∆PV), which was estimated from haemoglobin and haematocrit (Dill & Costill, 1974). Capillary blood sample collection was chosen due to athlete preference, non-invasiveness, reduced discomfort and convenience, and itis a reliable and accurate method (Ponampalam et al, 2012).…”
Section: Immunological Measuresmentioning
confidence: 99%
“…White blood cells (WBC) and WBC content (neutrophils, eosinophils, basophils, lymphocytes and monocytes) were measured and corrected for change in plasma volume (∆PV), which was estimated from haemoglobin and haematocrit (Dill & Costill, 1974). Capillary blood sample collection was chosen due to athlete preference, non-invasiveness, reduced discomfort and convenience, and itis a reliable and accurate method (Ponampalam et al, 2012).…”
Section: Immunological Measuresmentioning
confidence: 99%
“…There exists an unresolved conflict in the literature regarding the appropriateness of capillary blood draws vs venous draws for CBC measurements. While some authors have found significant variations in capillary blood , still others have found minimal variation . Indeed capillary blood draws are standard practice when testing neonate blood or other patients for whom standard blood draws are not possible .…”
Section: Methodsmentioning
confidence: 99%
“…Although erythrocyte related parameters such as haematocrit and haemoglobin concentration, have been found to be significantly higher in capillary samples (Daae et al 1988), leucocyte concentrations have provided conflicting results. Capillary samples have yielded higher (Schalk et al 2007;Yang et al 2001), lower (Bakhmetyev and Agafonova 2002) or not significantly different (Ponampalam et al 2012) results for the concentration of leucocytes when compared to venous samples. Furthermore, analysis of leucocyte sub-populations in capillary samples has also produced diverging results, where lymphocyte concentration (typically 30 % of circulating leucocytes) has been found to be increased (Daae et al 1988), decreased (Hollis et al 2012) or unaltered (Yang et al 2001) in comparison to results obtained from venous samples.…”
Section: Introductionmentioning
confidence: 92%